The Effect of Profit Sharing Financing, TPF and Capital on Net Profit through Revenue Sharing on Buses - Sugianto Sugianto; Yenni Samri Juliati Nst; Winda Anriani Siregar (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aims to determine how much influence the financing for the results, DPK and capital on net income mediated by revenue sharing. The sample used in this study is data 10 BUS in annual form from 2014 to 2019, and the approach used uses a quantitative approach. This study uses 60 samples that are processed using panel data regression analysis method using the views 9 application. The results of the analysis show that this study produces a coefficient of determination (R-square) in structural model I, which is 96.1% of the variable for profit sharing, TPF, and capital affects profit sharing income in Islamic commercial banks, while 3.9% is explained by other variables. The result of the coefficient of determination (R-square) model II is 22.6%, the variable of profit sharing, TPF, capital and revenue sharing affects the net profit in Islamic commercial banks, while 77.4% is influenced by other variables. This study shows that the financing for the results, TPF, capital and revenue sharing have a simultaneous effect on net income with a significance level of 0.001 <0.05. From the results of the indirect effect significance test, it was found that there was no significant indirect effect of the profit sharing variable, TPF and capital on net income through revenue sharing as an intervening variable in Islamic commercial banks. Capital and profit sharing income affect net income in Islamic commercial banks while 77.4% is influenced by other variables.